Incidence, Prevalence, and Health Care Outcomes in Idiopathic Intracranial Hypertension: A Population Study. (23rd February 2021) - Miah, Latif; Strafford, Huw; Fonferko-Shadrach, Beata; Hollinghurst, Joe; Sawhney, Inder M.S.; Hadjikoutis, Savvas; Rees, Mark I.; Powell, Rob; Lacey, Arron; Pickrell, William O.
Abstract : Objective: To characterize trends in incidence, prevalence, and health care outcomes in the idiopathic intracranial hypertension (IIH) population in Wales using routinely collected health care data. Methods: We used and validated primary and secondary care IIH diagnosis codes within the Secure Anonymised Information Linkage databank to ascertain IIH cases and controls in a retrospective cohort study between 2003 and 2017. We recorded body mass index (BMI), deprivation quintile, CSF diversion surgery, and unscheduled hospital admissions in case and control cohorts. Results: We analyzed 35 million patient-years of data. There were 1, 765 cases of IIH in 2017 (85% female). The prevalence and incidence of IIH in 2017 was 76/100, 000 and 7.8/100, 000/y, a significant increase from 2003 (corresponding figures = 12/100, 000 and 2.3/100, 000/y) ( p < 0.001). IIH prevalence is associated with increasing BMI and increasing deprivation. The odds ratio for developing IIH in the least deprived quintile compared to the most deprived quintile, adjusted for sex and BMI, was 0.65 (95% confidence interval 0.55 to 0.76). Nine percent of IIH cases had CSF shunts with less than 0.2% having bariatric surgery. Unscheduled hospital admissions were higher in the IIH cohort compared to controls (rate ratio 5.28, p < 0.001) and in individuals with IIH and CSF shunts compared to those without shunts (rate ratio 2.02, p < 0.01). Conclusions: IIH incidence and prevalence is increasing considerably, corresponding to population increases in BMI, and is associated with increased deprivation. This has important implications for health care professionals and policy makers given the comorbidities, complications, and increased health care utilization associated with IIH.